The Effectiveness Of Crystal Guava (Psidium guajava Linn) Leaf Extract As An Insecticide Againts Aedes aegypti: Efektivitas Ekstrak Daun Jambu Kristal (Psidium Guajava Linn.) Sebagai Insektisida Nyamuk Aedes aegypti - Satriyo Siswo Utomo; Yauwan Tobing Lukiyono; Irwan Sulistio; Agus Aan Adriansyah (Medicra (Journal of Medical Laboratory Science/Technology), 2025)
Aedes aegypti is a species of mosquito that acts as a vector for the dengue virus. Currently, control of this viral vector has been carried out using synthetic insecticides. However, continued use can lead to the emergence of resistance, necessitating efforts to address this issue. One possible approach is to use natural insecticides derived from plants. One plant considered suitable as a natural insecticide is the extract of crystal guava leaves (Psidium guajava Linn) because it contains bioactive compounds such as flavonoids, tannins, alkaloids, and saponins. The purpose of this study was to determine the effectiveness of using crystal guava leaf extract as a spray insecticide against Aedes aegypti mosquitoes. This study used an experimental method with a Control Group Post-Test Design. Ethanol extract of crystal guava leaves (Psidium guajava Linn) was prepared in several concentrations: 22.5%, 45%, and 90%. The spray was then observed on Aedes aegypti mosquitoes for 3, 6, and 24 hours. The concentration was then determined to determine the mosquito-killing power. Analysis was then performed using SPSS to determine the LC50 and LT50 values.